Neurodevelopmental Outcome at 12 Months of Postnatal Magnesium Sulphate Therapy for Perinatal Asphyxia (Journal of Nepal Paediatric Society, 2017)
Introduction: Postnatal magnesium therapy has been proposed as a novel neuroprotective agent for perinatal asphyxia. A few studies reported short term neurological benefit with magnesium. It is uncertain whether magnesium therapy has any long term effect on neurodevelopment.Material and Methods: We randomly assigned 120 term asphyxiated infants to receive either magnesium sulphate infusion or placebo postnatally in first 48 hours of life. Babies were treated as per the standard treatment protocol for asphyxia. Short term outcome at discharge was previously reported and a follow up evaluation at 12 months was done. The primary outcome was a composite of death or disability, developmental delay and neuromotor tone abnormality at 12 months.Results: Out of 120 infants, 69 infants had moderate-severe hypoxic-ischemic encephalopathy (HIE) during initial NICU stay. Among 69 infants with moderate-severe HIE, 41 infant could be followed up. Out of 41 infants, 22 were in magnesium group and 19 in placebo group. Of 22 infants assigned to magnesium therapy, 3(13.6%) died or survived with neurodevelopmental disability as compared with 5 of 19 infants (26.3%) assigned to placebo (p=0.32). The developmental outcome evaluated found developmental delay in 3 of 22 infants in magnesium group vs 5 of 19 infants in placebo group (p=0.32). Ameil-Tisonneuromotor tone assessment revealed tone abnormality in 3 of 22 infants in study group vs 4 of 19 infants in placebo group (p=0.53).Conclusion: Magnesium therapy for perinatal asphyxia may not result in favourable long term neurodevelopmental outcome, though no significant adverse effect has been documented.J Nepal Paediatr Soc 2016;36(3):256-262